Effect of eco-innovation on GSCM, CE capability, and performance of MSMEs - Dina Rosada, Maya; Kusmantini, Titik (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2025)
This study aims to determine and analyze the effect of eco-innovation on green supply chain management, circular economy capability, and firm performance of MSMEs. This is a survey study with a questionnaire as a data collection tool. The population in this study is the MSMEs in the processed salak culinary industry in Sleman Regency. The data used in this study are primary data from 50 respondents using purposive sampling. Hypothesis testing uses Partial Least Squares (PLS) with SmartPLS 4. The results of this study indicate that 1) eco-innovation has a positive and significant effect on firm performance, 2) eco-innovation has a positive and significant effect on green supply chain management, 3) eco-innovation has a positive and significant effect on circular economy capability, 4) green supply chain management has no significant effect on firm performance, 5) circular economy capability has a positive and significant effect on firm performance